Analysis of Guest Brand Switching Behavior at Kyriad Bumiminang Padang Hotel - Puji Intani; Nidia Wulansari (Pt. Threeple Herphi Educate, 2024)
This study aims to determine what factors influence brand switching at Kyriad Bumiminang Hotel Padang. This research uses a type of quantitative descriptive research using survey methods. The sampling method in this study used purposive sampling. Purposive sampling is a sampling technique with certain considerations. The sampling criteria were those who had stayed at the Kyriad Bumiminang Padang Hotel and were over 17 years old. The sample used was the guests of the Kyriad Bumiminang Padang Hotel, totaling 93 people. In addition, the data obtained is described, then a description of the research results is carried out using the TCR technique